The Role of Educational Supervision in Raising the Motivation of House Economy Students towards Vocational Education from The Point of View of Educational Supervisors in The Governorates of Ajloun and Jerash - Al-Qudah, Mithal AbdelHafez Saleem (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of educational supervision in raising the motivation of house economy students towards vocational education from the point of view of educational supervisors in the Governorates of Ajloun and Jerash. The researcher used the Descriptive approaches, study Sample consisted from (90) Female and male educational supervision, chosen randomly, to collect data Questioner used, which consisted (17) paragraph. The result of SPSS analysis shown that the degree of the role of educational supervision in raising the motivation of house economy students towards vocational education from the point of view of educational supervisors in the Governorates of Ajloun and Jerashwas High with average (4.12 out of 5), The finding also showed there was statistically significant differences at (α≤0.05) refers to educational supervision sex (male and female) in favor of female. In addition, there were no statistically significant differences refers to educational supervision years of experience.
Keywords: Educational Supervision; Motivation; House Economy; Vocational Education